Hydrothermally Treated Coals for Pulverized Coal Injection. Technical Progress Report, April 1995--June 1995 - Walsh, D. E.; Rao, P. D.; Ogunsola, O.; Lin, H. K. (University of Alaska Fairbanks, 1995)
This project is investigating the suitability of hydrothermally dried low-rank coals for pulverized fuel injection into blast furnaces in order to reduce coke consumption. Coal samples from the Beluga coal field and Usibelli Coal Mine, Alaska, are being used for the study. Crushed coal samples were hydrothermally treated at three temperatures, 275, 300 and 325degreesC, for residence times ranging from 10 to 120 minutes. Products have been characterized to determine their suitability for pulverized coal injection. Characterization includes proximate and ultimate analyses, vitrinite reflectance, TGA reactivity and thermochemical modeling. A literature survey has been conducted.